2020
DOI: 10.4149/neo_2020_190601n478
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein gp96 and CD4+ and CD8+ T-lymphocytes expression as prognostic factors in various molecular types of invasive breast carcinoma

Abstract: Breast carcinoma shows extensive clinical and molecular heterogenicity. Glycoprotein gp96 is considered a negative prognostic and predictive factor. Controversy exists over the prognostic role of tumor lymphocytic infiltrates. The goal of this study is to illustrate differences in gp96 and CD4+ and CD8+ T-lymphocytes expression among all immunohistochemical groups of breast carcinoma in relation to the clinical course and outcome of the disease. A retrospective observational study was conducted through process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Furthermore, through conducting in vitro and in vivo experiments, we found that gp96-containing exosomes increased paclitaxel-resistance in PS-BC cells, hinting that PR-BC cells delivered exosomal gp96 to increase paclitaxel-resistance in PS-BC cells. In addition, previous literatures report that cancer cells derived exosomes interact with immune cells to promote immune evasion during cancer pathogenesis ( 37 39 ), and researchers notice that gp96 is considered as biomarker for immune surveillance via influencing CD4 + and CD8 + T-lymphocytes ( 9 , 40 ), which are supported by our results that gp96-containing exosomes suppressed cell viability in the CD8 + T cells, which is the main immune cells that recognize tumor antigens ( 35 , 36 ). Also, we verified that extracellular gp96 triggered pyroptotic cell death in CD8 + T cells, which is indirectly validated by the available information that gp96 activated NLRP3 inflammasome in the antigen presenting cells (APCs) ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, through conducting in vitro and in vivo experiments, we found that gp96-containing exosomes increased paclitaxel-resistance in PS-BC cells, hinting that PR-BC cells delivered exosomal gp96 to increase paclitaxel-resistance in PS-BC cells. In addition, previous literatures report that cancer cells derived exosomes interact with immune cells to promote immune evasion during cancer pathogenesis ( 37 39 ), and researchers notice that gp96 is considered as biomarker for immune surveillance via influencing CD4 + and CD8 + T-lymphocytes ( 9 , 40 ), which are supported by our results that gp96-containing exosomes suppressed cell viability in the CD8 + T cells, which is the main immune cells that recognize tumor antigens ( 35 , 36 ). Also, we verified that extracellular gp96 triggered pyroptotic cell death in CD8 + T cells, which is indirectly validated by the available information that gp96 activated NLRP3 inflammasome in the antigen presenting cells (APCs) ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…report that non-small cell lung cancer (NSCLC) derived PD-L1 containing exosomes promote CD8 + T cell death ( 35 ). Interestingly, gp96 is reported to be closely associated with immune cells infiltration in BC ( 9 , 40 ). Researchers notice that gp96 affects CD4 + and CD8 + T-lymphocytes in various types of invasive breast carcinoma ( 40 ), and extracellular gp96 has been considered as biomarkers for immune surveillance and immune evasion ( 9 ).…”
Section: Backgroundsmentioning
confidence: 99%
See 1 more Smart Citation
“…A tumor is considered HER2 positive only if it is concluded that the gene which codes for HER2 protein synthesis is amplified[4, 6]. The common denominator of the development of cancer and autoimmune/neurodegenerative diseases is chronic inflammation, where the immunosuppressive environment is crucial [7-9]. Growing evidence supports the hypothesis that the local inflammatory processes modulate the microenvironment, which is the key trigger of the molecular etiopatogenetic mechanisms of tumor development [9-11].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation mediators transform normal cells by activating oncogenes or getting rid of the anti-oncogenic activity, inducing tumor progression of preneoplastic lesions, apoptosis resistance, and differentiation [9, 12]. The immunosuppressive microenvironment is largely achieved by the action of infiltrating leukocytes, which constitute a large percentage of cellular populations in tumor tissue [7, 12, 13].…”
Section: Introductionmentioning
confidence: 99%